1994
DOI: 10.1136/pgmj.70.819.37
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin treatment and migraine

Abstract: Summary:A patient suffering from migraine, whose symptoms were abolished by warfarin therapy, is reported. Warfarin was prescribed for deep vein thrombosis and the frequency of the patient's headache improved remarkably during the anticoagulant therapy. Because of the unusual nature of the response to anticoagulant therapy, warfarin was reintroduced on a double blind (versus placebo) basis and once again abolished the headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…38 Thus, the improvement that we detected in both groups was well expected. In earlier studies, we and others observed a greater enhancement in QoL in patients having lower baseline scores, 9,39 which rationalizes the greater degree of QoL improvement in group 1 than in group 2, in this study. Lack of substantial change in bodily pain in the SF-36 scales can be attributed to age-related comorbidities, such as osteoporosis, arthritis, joint replacement in our mostly elderly study population.…”
Section: Improvement In Qolmentioning
confidence: 54%
See 1 more Smart Citation
“…38 Thus, the improvement that we detected in both groups was well expected. In earlier studies, we and others observed a greater enhancement in QoL in patients having lower baseline scores, 9,39 which rationalizes the greater degree of QoL improvement in group 1 than in group 2, in this study. Lack of substantial change in bodily pain in the SF-36 scales can be attributed to age-related comorbidities, such as osteoporosis, arthritis, joint replacement in our mostly elderly study population.…”
Section: Improvement In Qolmentioning
confidence: 54%
“…8,9 Warfarin is routinely prescribed to patients undergoing radiofrequency CA to prevent thromboembolic events. Therefore, our study also explored the impact of therapeutic warfarin on the prevalence and clinical course of migraine in patients with or without a previous history.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 99%
“…[1][2][3] Two recent cases involved patients aged 71 years 1 and 68 years, 2 the latter reporting that substitution of warfarin by placebo resulted in the return of migraine attacks. Robbins reported that migraine attacks suffered by three young females with high levels of anticardiolipin antibodies decreased during treatment with warfarin.…”
Section: Commentsmentioning
confidence: 99%
“…Key words: anticoagulation, impact, migraine, ergotamine, sumatriptan, consumption Abbreviations: DDDs defined daily doses, OAC oral anticoagulation with coumarin derivatives, ASA acetylsalicylic acid ( Headache 2001;41:768-773) A few case reports have described a complete resolution of migraine or a substantial reduction in frequency and intensity of migraine attacks in migraineurs with or without aura during treatment with oral anticoagulant drugs, such as warfarin or acenocoumarol. [1][2][3][4] In addition, a recent patient questionnaire study in 400 subjects treated with acenocoumarol for nonneurological indications revealed that oral anticoagulation produced improvement of headache in 63% of patients with migraine versus 38% of patients with nonmigrainous headache. 5 Although the…”
mentioning
confidence: 99%
“…[1][2][3][4] In addition, a recent patient questionnaire study in 400 subjects treated with acenocoumarol for nonneurological indications revealed that oral anticoagulation produced improvement of headache in 63% of patients with migraine versus 38% of patients with nonmigrainous headache. 5 Although the underlying mechanism associated with the possible improvement of migraine symptoms due to coumarin therapy has not been fully elucidated, there is evidence that during migraine attacks there is an increase in platelet aggregability and plasma coagulability.…”
mentioning
confidence: 99%